Digital Newspaper : An Analysis of Technology Acceptance Model â€“ Case Study : Student of Atma Jaya University Yogyakarta - Lumbantobing, Mutiara; Setyohadi, Djoko Budiyanto; Santoso, Albertus Joko (Journal of Information Technology and Computer Science, 2019)
Â Todays, the newspaper has been converging from print to digital. The advantages of the digital newspaper have made the digital newspaper a top choice especially for the student as a digital native group. The purpose of this study is to know and explain the acceptance of user (students) to the digital newspaper. This study proposed a theoretical framework that includes the core constructs in TAM: namely, Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Use (ATU), Behaviour Intention to Use (BIU) and Actual Use (AU). The statistical test method is statistical validity, reliability, normality, and test the influence of factors using Structural Equation Model (SEM). Data were obtained through questionnaires distributed to 100 UAJY students of Atma Jaya University Yogyakarta (UAJY) respondents from 5 faculties. The overall hypothesis proposed in this study is accepted, namely: Perceived Ease of Use (PEOU) has a positive effect on Perceived Usefulness (PU); Perceived Ease of Use (PEOU) has a positive effect on Attitudes Toward Use (ATU); Perceived Usefulness (PU) has a positive effect on Behavioral Intention to Use (BIU) Attitude (ATU) has a positive effect on Behavioral Intention to Use (BIU) ); Behavior Intention to use (BIU) has a positive effect on actual using (AU) digital newspaper.